Firearm Training System by Laser gun - Takopueak, Nopporn; Sutthinet, Chalin; Phetchakul, Toempong (My University, 2023)
This research presents a combat system with weapons, laser guns and electronic armor. Practicing firearms tactics results in shooting and maneuvering skills. The system consists of a laser gun that can determine the amount of ammunition used. The target of the armor has a sensor that receives laser light emitted by the gun. The guns and targets are controlled via a wireless network with a Node Micro Controller Unit (NodeMCU) connected to broker and can be displayed via computers, mobile phones and tablets. The IoT system uses protocol MQTT, the system used to store data on both sides of the device for response to the loss of network connection. The training is a gun fight between two players. The training is gun fighting between two players shooting guns against each other. The referee, commander and the audience can track the score of both players in real time. The training is safe to reduce the accidents of the practice also reduces the cost of training and can be practiced both indoors and outdoors.
Keywords: ammo; armor; battle; bullet; defence; IoT; laser gun; military; MQTT; NodeMCU; shooting training; target